Quantized doping of CdS quantum dots with twelve gold atoms. Issue 52 (7th June 2021) - Yu, Junlai; Zhang, Hui; Xu, Wenhao; Liu, Guangnan; Tang, Yun; Zhao, Dongyuan
Abstract : Through a bottom-up strategy, CdS quantum dots (QDs) doped with 12 gold atoms in each nanocrystal (NC) were prepared by cation exchange reactions. Abstract : Through a bottom-up strategy, CdS quantum dots (QDs) doped with 12 gold atoms in each nanocrystal (NC) were prepared by cation exchange reactions. The (Au12 ) dopants inside the CdS matrix were directly observed using Cs-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images and quantitatively confirmed using the inductively coupled plasma atomic emission spectroscopy (ICP-AES) data. With a photoluminescence quantum yield (PLQY) of 37.5%, the as-prepared (Au12 )@CdS QDs emitted light at 635 nm. Due to the injection of excited electrons from the lowest unoccupied molecular orbital (LUMO) of dopants to the conduction band (CB) of CdS, multiple fine peaks were observed in the photoluminescence excitation (PLE) spectra. By using clusters as starting materials, we demonstrate a universal approach for the precise tailoring of dopants and provide a pathway for band energy engineering of doped QDs.